MATCHMAKING AND MARRIAGE OF THE CIRCASSIANS IN THE MIRROR OF FOLKLORE - L. A. GUTOVA (Кавказология, 2019)
The article is devoted to the comparative analyses of ethnographic information about matchmaking and marriage in the traditions of Adyghs and their reflection in such genres of folklore as an archaic Nart epic, fairy tale and historical-heroic epic. The purpose of the work is determined by the task to establish the meaning and main poetic features of the verbal component in rituals associated with such an important stage of the life cycle as matchmaking and marriage.As a general regularity, it is established that the main features of really existing or existing customs found in folklore artistic reflection. Since folklore is primarily an art, there can be direct parallels and divergences between traditions in real life and representations in the context of works of art, sometimes so obvious, that folklore descriptions cannot correspond to reality. In different genres, they appear in accordance with the established system of artistic conventions in this area and are perceived as fiction. So for archaic epic in some cases it is characteristic that the marriage remained the second storyline on the background of the main feat, in others – it is closer in function to the cultural feat and thus comes to the fore of the narrative. The tale presents a greater variety of functions – from the secondary motive of matchmaking and marriage to the motive of procuring the bride as an adventurous crime. The closest thing to reality is the motif in the context of historical ad heroic songs and legends.